IoT-TSim: A Lightweight Discrete-Event Simulator for Gateway Queueing and Processing Dynamics in IoT - Alves, Melissa; Barbosa, Vandirleya; Cerqueira, Eduardo; Rosário, Denis; Fé, Iure; Andrade, Ermeson; Silva, Francisco Airton (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Internet of Things (IoT) architectures with many devices sending data to an edge gateway are common in monitoring and telemetry applications, where many design decisions depend primarily on the temporal behavior of message flows rather than on physical constraints. This paper presents a lightweight, time-oriented discrete-event simulator that models IoT devices as stochastic message sources and the gateway as a finite-capacity system with parallel processing. Simulation results show that increasing the number of devices accelerates gateway saturation, leading to sharp increases in end-to-end delay and packet loss. In contrast, increased gateway parallelism delays saturation and raises the maximum achievable throughput, supporting quantitative gateway dimensioning and traffic planning.